Real-time macroeconomic data and ex ante predictability of stock returns - Jörg Döpke; Daniel Hartmann; Christian Pierdzioch (Deutsche Bundesbank, 2006)
We report results on the ex ante predictability of monthly excess stock returns in Germany using real-time and revised macroeconomic data. Our real-time macroeconomic data cover the period 1994-2005. We report three results. 1) Real-time macroeconomic data did not contribute much to ex ante stock-return predictability. 2) The performance of an investor who had to rely on noisy real-time macroeconomic data would have been comparable to the performance of an investor who had access to revised macroeconomic data. 3) In real time, it is important for an investor to know which real-time variable to use for predicting stock returns.
Keywords: G11; E44; C53; 330; Ex ante predictability of stock returns; real-time macroeconomic data; performance of investment strategies; Germany; Börsenkurs; Kapitalertrag; Prognoseverfahren; Konjunkturstatistik; Konjunkturindikator; Schätzung; Theorie; Deutschland